Faktor yang Berhubungan dengan Kepemilikan Jamban Sehat di Desa Nambangan Kidul Manguharjo Kota Madiun - Eny Pemilu Kusparlina (Jurnal Delima Harapan, 2021)
ABSTRACT The World Bank states that the 2018 data 22% of Indonesian people has not had a sanitation facility (latrine). The existence of latrines in Indonesia, according to World Bank data in 2015 about 22% of Indonesia's population does not have latrines. The coverage of national guard to urban areas with 79% and 49% for rural areas. Most of the sludge removal used the river or dug wells which do not have the requirements of health latrine and contiminate the ground water. Based on the data obtained from the Health Center Community Manguharjo in 2019 of 855 homes were inspected as many as 530 households, households have basic sanitation facilities such as latrines in the Health Center Community Manguharjo downstream for 420 households or 79%. This study aims to determine the relationship between the factors of income, knowledge, and attitude, with the ownership of latrines in Madiun City, Manguharjo. The research method used observational design with cross sectional approach. The sample are mothers who have children under five do not have latrines that 64 respondents. The sampling technique used random sampling. Statistical analysis used chi square test. Decision of research hypothesis testing based on the significance level of 5% (p = 0.05) and confidence interval (CI) 95%. The result showed that there are relationship between income and the latrine ownership (p = 0.037), knowledge (p = 0.037) and attitude (p = 0.037). The result showed no relationship between education (p = 0196), and the role of health care workers (p = 1.000) with the ownership of latrines in the Madiun City, Manguharjo. Keywords: Latrine, income, knowledge, attitude.